2015
DOI: 10.1016/j.mib.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics and the developing infant gut microbiota and resistome

Abstract: The microbial communities colonizing the human gut are tremendously diverse and highly personal. The composition and function of the microbiota play important roles in human health and disease, and considerable research has focused on understanding the ecological forces shaping these communities. While it is clear that factors such as diet, genotype of the host, and environment play important roles in adult gut community composition, recent work has emphasized the importance of early-life assembly dynamics in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
134
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(142 citation statements)
references
References 59 publications
(99 reference statements)
5
134
0
3
Order By: Relevance
“…Accordingly, during the first days following birth, the infants' microbiota may be more sensitive to antibiotic treatment due to a very simple and fragile bifidobacterial community, which appears to be unable to cope with a high level of antibiotic administration. Thus, the particular antibiotic administered to the newborn may bring about an intestinal microbiota disturbance that can prevent or delay subsequent development of a normal microbiota (38).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, during the first days following birth, the infants' microbiota may be more sensitive to antibiotic treatment due to a very simple and fragile bifidobacterial community, which appears to be unable to cope with a high level of antibiotic administration. Thus, the particular antibiotic administered to the newborn may bring about an intestinal microbiota disturbance that can prevent or delay subsequent development of a normal microbiota (38).…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12][13][14] One of the most common perturbations during this period, antibiotic therapy, 13,15 can substantially alter the gut microbiota and infant physiology. 10,[16][17][18][19][20][21] Because preterm infants are at high risk for infection, antibiotics are the most commonly prescribed medications in neonatal intensive care units (NICUs) in the United States ( Fig. 1) 15,22,23 accounting for 3 of the top 6 medications with the greatest relative increase in use in NICUs in the United States between 2005 and 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Although it was reported that other pharmacological treatment, such as antidiabetic medication, can alter the GM [100], the drugs that primarily play the most significant action on the GM are the antibiotics [71,91,101]. Antibiotic administration, especially in the case of infants [102][103][104][105][106], in whom their use has been related to higher predisposition to infant obesity. The effects of antibiotics on the GM have been investigated actively in recent years, mainly using experimentation animals exposed to various concentrations of antibiotics to evaluate how they affect the microbiota and thus its microbiome.…”
Section: Specific Effects Of Antibiotics On the Human Gut Microbiotamentioning
confidence: 99%
“…Antibiotics are one of the most prescribed drugs in human medicine, particularly in pediatrics and neonatal nursing in developed countries [104,111]. The effect of these drugs on the human GM, both during and after the treatment has been widely investigated in recent years, although it is not yet fully understood [29].…”
Section: Specific Effects Of Antibiotics On the Human Gut Microbiotamentioning
confidence: 99%